International Comparisons of Public Sector Efficiency – DEA Methodology - Lovre, Ivan; Jotic, Jelena (Industrija, 2016)
The paper analysed and compared the public sector efficiency of the Republic of Serbia with the countries in the region, the new members of the European Union and the EU countries. The public sector efficiency is analysed by relevant methodology and the linear programming model - DEA (Data Envelopment Analysis). The aim of this research is analysis and comparison of the efficiency of the public sector of the Republic of Serbia with the European Union members are used for determining the level of efficiency, but also the need for state’s intervention in Republic Serbia. Significant inefficiency of the public sector of the Republic of Serbia resulted in negative effects on the stability of the public finance system. The functioning of the Serbian public sector is marked with budget deficits followed by a constant growth of external and internal debt. Unreformed public sector will lead to the failure of fiscal consolidation, while implemented fiscal consolidation measures will not be effective without the reform of the public sector. The study indicates possibilities for reducing public spending by around 25% without reducing the efficiency of the public sector, which would be sufficient for elimination of the budget deficit.